2022
DOI: 10.3389/fsurg.2022.955987
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of single and double incision for L4/5 and L5/S1 double-level percutaneous interlaminar lumbar discectomy

Abstract: ObjectiveThis study aims to investigate the clinical outcome of single and double incision for double-level percutaneous interlaminar lumbar discectomyMethodsA retrospective analysis was performed involving patients with L4/5 and L5/S1 double-level lumbar disc herniation who received percutaneous interlaminar lumbar discectomy (PEID) in our hospital from January 2017 to December 2020. These enrolled patients were divided into single- and double-incision groups, with 25 patients in each group. We compared the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…We performed a battery of behavioral phenotyping tests to assess general health and physical indices of stress, pain-like behaviors at sites local and distant to the site of injury, spontaneous pain-like behaviors, and psychosocial behavioral testing as a means to also collect information on general well-being ( 69 72 ). Similar to other groups examining symptoms associated with IVD injury in rodent models, we examined general health by assaying body weight across time ( 67 ), evoked hypersensitivity to pressure at the site of injury ( 25 , 29 , 36 ) using a pressure algometer applied to the lower back ( 67 ), evoked pain-like behaviors at sites distant to the site of injury using the same pressure algometer but applied to the upper thigh and von Frey monofilament assays on the hindpaws ( 21 , 25 , 28 , 29 , 36 , 61 , 67 , 73 ), and spontaneous pain-like behaviors such as reduced/impaired locomotion during open field gait assays ( 29 , 51 ) and grooming changes post-IVD injury ( 15 , 74 ) as changes in grooming may be indicative of stress and pain in rodents ( 15 , 71 , 74 ). We also examined cold sensitivity as similarly performed by others examining symptoms associated with IVD injury ( 36 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a battery of behavioral phenotyping tests to assess general health and physical indices of stress, pain-like behaviors at sites local and distant to the site of injury, spontaneous pain-like behaviors, and psychosocial behavioral testing as a means to also collect information on general well-being ( 69 72 ). Similar to other groups examining symptoms associated with IVD injury in rodent models, we examined general health by assaying body weight across time ( 67 ), evoked hypersensitivity to pressure at the site of injury ( 25 , 29 , 36 ) using a pressure algometer applied to the lower back ( 67 ), evoked pain-like behaviors at sites distant to the site of injury using the same pressure algometer but applied to the upper thigh and von Frey monofilament assays on the hindpaws ( 21 , 25 , 28 , 29 , 36 , 61 , 67 , 73 ), and spontaneous pain-like behaviors such as reduced/impaired locomotion during open field gait assays ( 29 , 51 ) and grooming changes post-IVD injury ( 15 , 74 ) as changes in grooming may be indicative of stress and pain in rodents ( 15 , 71 , 74 ). We also examined cold sensitivity as similarly performed by others examining symptoms associated with IVD injury ( 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, the study primarily focused on the intervention effects of a drug rather than characterizing differences between single vs. multi-level injury with respect to disc height, histopathology, and pain-related behaviors, among other features, which could have important clinical implications. In humans, the herniation of two lumbar discs (termed tandem disc herniation) on first presentation has a relative low incidence rate, but is not rare ( 29 ). That said, migration of the lumbar disc herniation to an adjacent disc (either caudally or rostrally) is a significant predictor of disc herniation recurrence and occurs in up to 19% of patients ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…LDH is often accompanied by nerve compression symptoms such as sciatica, leg pain, or lower back pain. In clinic, we found that it is not rare for patients to develop double-level LDH, while patients who fail to receive stepwise conservative treatment always need further surgical interventions [ 2 ]. Conventional open lumbar discectomy (COLD) and percutaneous endoscopic lumbar discectomy (PELD) are the common surgical approaches for LDH [ 3 ].…”
Section: Introductionmentioning
confidence: 99%